BRCA1 is involved in sustaining rapid antler growth possibly via balancing of the p53/endoplasmic reticulum stress signaling pathway - Qianqian Guo; Zhen Wang; Jiping Li; Chao Ma; Junjun Zheng; Hengxing Ba; Guokun Zhang; Chunyi Li (Biology Direct)
Abstract Background Regeneration is the preferred approach to restore the structure and function after tissue damage. Rapid proliferation of cells over the site of damage is integral to the process of regeneration. However, even subtle mutations in proliferating cells may cause detrimental effects by eliciting abnormal differentiation. Interestingly deer antlers, arguably the fastest regenerating mammalian tissue, have not been reported, thus far, to grow malignant tumors. They provide a mammalian model to understand the possible mechanism by which rapid regeneration is achieved while avoiding the development of malignancies. Antler regeneration is based on the proliferation and differentiation of antler stem cells (AnSCs). Results We identified 39 hub genes which may function in regulating the balance between rapid proliferation and genomic stability in the AnSCs during antler regeneration. Among these 39 genes, the tumor suppressor gene, BRCA1, was found to be more sensitive to DNA damage in the AnSCs compared to that in the deer somatic cells, and BRCA1 deletion in the AnSCs via CRISPR/Cas9 resulted in significantly higher levels of DNA damage. Lack of BRCA1 promoted cell apoptosis and cell senescence and inhibited cell proliferation and cell self-renewal. RNA-seq results showed that in the absence of BRCA1, the p53 signaling pathway was significantly up-regulated. Associated with this change, the cell apoptosis and cell senescence-relevant-genes, CDKN1A, CDKN2A and Fas were over expressed, but the expression of cell-cycle-progression-related genes was inhibited. In addition, BRCA1 expression levels were found to be more sensitive to endoplasmic reticulum stress (ERS) in the AnSCs compared to the somatic cells. Deletion of BRCA1 gene aggravated ERS and ERS-induced cell apoptosis. Conclusions Our results revealed that BRCA1 is involved in sustaining rapid antler growth possibly via promotion of DNA damage repair that acts to maintain genome stability while protecting cells from p53/ERS-induced cell death. Understanding the mechanisms underlying the role played by BRCA1 in the process of antler regeneration is of great significance not only for regenerative medicine, but also for the understanding of cancer development.